Proactive management of lay-offs, retirement and other post-employment concerns - Sibal, Jorge V. (2003)
Not much has been written about separation and post-employment concern such that when companies need to dismiss employees for varying reasons - intense competition, introduction of new technology, transfer of location, etc. - they find themselves groping in this inevitable last phase of HRM functions. This paper will present post-employment programs and practices, and documented case studies of companies that have successfully implemented some of these interventions. Among the common post-employment HR programs are the following: outplacement counseling services; skill building for post - employment which include livelihood and entrepreneurship; knowledge in investing money in banks, quasi-banks and corporations/cooperatives; private pension funds such as provident fund, employee stock option plan; and granting of retirement benefits under SSS or GSIS, among others.
Keywords: Postemployment benefits; Retirement benefits; Retirement planning